2022
DOI: 10.1159/000525845
|View full text |Cite
|
Sign up to set email alerts
|

The Serum Levels of IL-36 in Patients with Coronary Artery Disease and Their Correlation with the Serum Levels of IL-32, IL-6, TNF-α, and Oxidative Stress

Abstract: <b><i>Introduction:</i></b> Atherosclerosis is a chronic inflammatory process maintained during all stages of the disease by several proinflammatory mediators, such as cytokines and chemokines. Interleukin (IL)-36 cytokines are proinflammatory and have an essential role in innate and adaptive immunity, but the role of IL-36 has not been determined in coronary artery disease (CAD). This study aimed to measure the serum levels of IL-36 in patients with CAD and their association with the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Oxidative stress and inflammation are considered risk factors for serious diseases such as heart diseases and cancers (35)(36)(37)(38). Various studies reviewed in this study showed that Ber attenuated DOX-induced nephrotoxicity by reducing total reactive oxygen species (ROS), lipid peroxides, NF-κB p65, interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and caspase-3 (39).…”
Section: Discussionmentioning
confidence: 97%
“…Oxidative stress and inflammation are considered risk factors for serious diseases such as heart diseases and cancers (35)(36)(37)(38). Various studies reviewed in this study showed that Ber attenuated DOX-induced nephrotoxicity by reducing total reactive oxygen species (ROS), lipid peroxides, NF-κB p65, interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and caspase-3 (39).…”
Section: Discussionmentioning
confidence: 97%
“…It is well known that the pathways include immune system [55], TCR signaling [56], cytokine signaling in immune system [57], degradation of the extracellular matrix [58], extracellular matrix organization [58], metabolism of lipids [59] and metabolism [60] [110], GPR174 [111], CCR4 [112], POU4F2 [113]. CCR2 [114], IL2RB [115], CCL4 [116], CCL24 [117], FASLG (Fas ligand) [118], CD24 [119], TDGF1 [120], CD28 [121], IL7R [122], CYP11B1 [123], CCL5 [124], CCL3 [125], LTF (lactotransferrin) [126], GPNMB (glycoprotein nmb) [ HGF (hepatocyte growth factor) [135], TRPM8 [136], DIO3 [137], SIGLEC1 [138], TTR (transthyretin) [139], IL24 [140], F13A1 [141], IL9 [142], VEGFA (vascular endothelial growth factor A) [143], RASAL1 [144], ADM (adrenomedullin) [145], ANGPTL4 [146], CHI3L1 [147], LDB3 [148], CNP (2',3'-cyclic nucleotide 3' phosphodiesterase) [149], HES6 [150], CMTM5 [151] SEMA4D [160], GLUL (glutamate-ammonia ligase) [161], S1PR5 [162], FN3K [163], MEIS1 [...…”
Section: Construction Of the Tf-hub Gene Regulatory Networkmentioning
confidence: 99%
“…Although numerous risk factors for CAD have been identified and studied, including circulating miRNAs, blood lipids, cholesterol, glucose, and inflammatory factors [ [17] , [18] , [19] , [20] ], utilizing these factors to predict CAD risk is not yet common. This is due to the large variability of some of these factors in different individuals, particularly inflammatory factors, which have been shown to be associated with CAD risk but are also sensitive to environmental factors such as diet and infection.…”
Section: Introductionmentioning
confidence: 99%